Knowledge Management Philosophy: Communication as a Strategic Asset in Knowledge Management - Johannessen, Jon-Arild (Emerald points, 2020)
Knowledge Management is an important part of all business, and yet the discipline lacks a philosophy based on systemic thinking. Exploring this gap, expert author Jon-Arild Johannessen continues his research on knowledge management with the groundwork for a new philosophy.